Lipase/acyltransferase-catalysed interesterification of fat blends containing n-3 polyunsaturated fatty acids - Osório, Natália Melo (2015)
The lipase/acyltransferase from Candida parapsilosis is an original biocatalyst that preferentially catalyses alcoholysis over hydrolysis in biphasic aqueous/organic media. In this study, the performance of the immobilised biocatalyst in the interesterification in solvent-free media of fat blends rich in n-3 polyunsaturated fatty acids (n-3 PUFA) was investigated. The interesterification activity of this biocatalyst at a water activity (aw) of 0.97 was similar to that of commercial immobilised lipases at aw values lower than 0.5. Thus, the biocatalyst was further used at an aw of 0.97. Response surface modelling of interesterification was carried out as a function of medium formulation, reaction temperature (55–75 7C) and time (30– 120 min). Reaction media were blends of palm stearin (PS), palm kernel oil and triacylglycerols (TAG) rich in n-3 PUFA (“EPAX 4510TG”; EPAX AS, Norway). The best results in terms of decrease in solid fat content were observed for longer reaction time (.80 min), lower temperature (55–65 7C), higher “EPAX 4510TG” content and lower PS concentration. Reactions at higher temperature led to final interesterified fat blends with lower free fatty acid contents. TAG with high equivalent carbon number (ECN) were consumed while acylglycerols of lower ECN were produced